A Monitoring Application for Screening or Early Detection of High-Risk Pregnant Women Using Spring Boot and Flutter Frameworks - Khairullah Zikri; Dwijoko Purbohadi; Aprilia Kurnianti (Emerging Information Science and Technology, 2021)
Pregnancy is still a major health issue at present. Statistics demonstrate an annual increase in pregnancies. Monitoring pregnant women involves undergoing regular checkups to verify the fetus’s health. However, many midwives still manually enter data in ledgers. Therefore, this study designed an application to assist midwives in saving and displaying data to monitor the health of pregnant women, allowing the stored data to be easily obtained and saving midwife storage space. This application is exclusively accessible to midwives due to the restricted periodic health checkups for pregnant women. This application was developed using the spring boot and flutter frameworks. In the final stage, testing was performed on the designed features.Keywords: .